1974
DOI: 10.1021/je60061a003
|View full text |Cite
|
Sign up to set email alerts
|

Tetramido derivatives of glyoxal

Abstract: Nine glyoxal tetramides (III) were prepared by acid-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Synthesis of imidazolidines through the cyclocondensation of diamines, bisamides and urea derivatives with aqueous glyoxal and other appropriate carbonyl compounds has been the subject of numerous investigations [1][2][3][4][5][6][7][8][9][10]. In 1962, Slezak et al reported the acid-catalyzed reaction of urea derivatives with aqueous glyoxal leading to the formation of the corresponding glycolurils 1 (Figure 1) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of imidazolidines through the cyclocondensation of diamines, bisamides and urea derivatives with aqueous glyoxal and other appropriate carbonyl compounds has been the subject of numerous investigations [1][2][3][4][5][6][7][8][9][10]. In 1962, Slezak et al reported the acid-catalyzed reaction of urea derivatives with aqueous glyoxal leading to the formation of the corresponding glycolurils 1 (Figure 1) [11].…”
Section: Introductionmentioning
confidence: 99%